Coronavirus in Latin America: The effects of government measures along different phases of the pandemic - Ratto, Maria Celeste (2021)
Covid-19 pandemic has left more than 30 million confirmed cases and one million deaths. The challenge has been enormous, different governments have adopted diverse measures in order to reduce the number of new infections and deaths, and the consequences in economic terms. The scenarios have been changing and successful strategies have to change because they loose effectiveness or became obsolete. The aim of this paper is to analyze the effects that different kinds of measures taken by Latin American governments had on the daily new cases. The main hypothesis of this work is that the effect of the government responses to Covid-19 has varied throughout the different phases of the pandemic. The countries analyzed were Argentina, Bolivia, Chile, Colombia, Costa Rica, El Salvador, Guatemala, Honduras, México, Panamá, Peru, Paraguay, Dominican Republic and Uruguay. A Time Series Cross Section analysis was performed, to allows studying the evolution of the number of daily cases over time and by country. The period of time studied is from the day the first case of corona virus was registered in a country, until September 14, 2020. We used data from COVID-19 Dashboard database of Johns Hopkins University, and the Oxford COVID-19 Government Response Tracker dataset.